A description of the final stadium larva of Calicnemia gulinensis Yu & Bu, 2008 (Odonata: Platycnemididae). Issue 2 (2nd April 2020) - Chen, Xueyi; Yu, Xin
Abstract : The final stadium larva of Calicnemia gulinensis is described here for the first time. The larva can be distinguished from other known species of the genus Calicnemia by the arrangement of setae on premental edges and the number of setae on labial palpi. The important morphological characters of the caudal gills and the possible functional adaptation are discussed briefly.